Предметна відеозйомка - Нефьодова, І. А. (ХНУРЕ, 2024)
This work is devoted to the process of creating product video and its artistic aspects. In contemporary marketing strategies, product video shoots have become essential, providing businesses with a platform to exhibit their products, engage with consumers, and drive sales. A product video shoot involves the careful planning, execution, and editing of video content aimed at highlighting the features and benefits of a particular product. From conceptualization and scriptwriting to filming and post-production, each stage of the video production process plays a crucial role in shaping the final product. Companies are increasingly leveraging video marketing to promote their products and enhance brand visibility.
Keywords: предметна відеозйомка; відеозйомка